Deep sounding (2MHz) radar profiles over three ice rises (Blåskimen Island, Kupol Ciolkovskogo and Kupol Moskovskij) in Western Dronning Maud Land - Matsuoka, Kenichi (Norwegian Polar Institute, 2016)
This dataset consists of unprocessed 2MHz radar profiles over three ice rises Blåskimen Island (four profiles), Kupol Ciolkovskogo (four profiles) and Kupol Moskovskij (three profiles), Fimbul Ice Shelf, western Dronning Maud land. Data includes corresponding GPS information along each profile. The scientific objective is to calculate the ice thickness and the bed profile of the ice rise. It can also be used to study engalical stratigraphy in the profiles. The data are provided in MATLAB (.mat) file format. Blåskimen Island: IRD_deep_radar.mat Kupol Ciolkovskogo: IRB_deep_radar.mat Kupol Moskovskij: IRC_deep_radar.mat Each consisting struct-class variables for each profile as ‘Profile_1’, Profile_2’ etc. Profile_1 includes - - ‘data’ matrix with radar amplitude data. - ‘twt’ array with two way travel time for the radar signal in seconds - ‘lat’ and ‘lon’ are in decimal degrees - ‘x’ and ‘y’ show the coordinates, and ‘z’ shows elevations. All are in the unit of meters. - ‘dist’ shows the distance at a point from the start in meters. The data was collected by towing the system with a speed of 8-10 kmph. The offset between the receiver and transmitter is ~119 meters. There are 1024 samples in fast direction. See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.